Implementation Of the Analytic Hierarchy Process (AHP) Method in Determining Priorities for Solutions to Zakat Management Problems in Lumajang Regency - Mustaan, Abdullah Gufronul; Muhdir, Ibnu; Noipom, Tawat (Jurnal Magister Ekonomi Syariah, 2023)
Zakat can appear as a sharia economic instrument that can balance an economy and fix the severity and depth of poverty. The potential of zakat in Lumajang is quite significant, but the total zakat funds collected are still far from the total target and potential of existing zakat funds. From there it can be seen that serious problems create gaps in the management of zakat. This study aims to provide a map of priority problems in zakat management and priority solutions that can be given to zakat management in Lumajang Regency. The method to find the priority scale used in this study is the Analytic Hierarchy Process (AHP) involving four expert informants in the field of zakat. The results of the study reveal that the priority problems and solutions for zakat management in Lumajang Regency are three aspects, namely OPZ, Muzaki/Mustahik, and regulatory aspects. The most priority problem is from the OPZ aspect with a priority value of 0.638425 and the priority solution is also occupied by the OPZ cluster with a priority score of 0.581459.